Thermal and Structural Properties of Some Chelate Polymers. - ASWAR, A.S.; BHAVE, N.S. (Asian Journal of Chemistry, 2010)
New polychelates of Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) have been synthesised from Schiff base derived from 4, 4´-dihydroxy-3, 3´-diacetyl biphenyl and 1, 5-diaminonaphthalene and characterized by elemental analysis, magnetic and spectral data and thermal studies. The thermal stabilities of the polychelates obtained from thermograms is in the order Fe > Cu > Ni > Mn > Co, while the activation energy follows the order Fe > Mn > Ni > Cu > Co.